2007
DOI: 10.1007/s10886-007-9278-1
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy on Bark of Downed Logs of Chamaecyparis Obtusa sieb. and Zucc. var. formosana (Hayata) Rehder

Abstract: Chamaecyparis obtusa Sieb. and Zucc. var. formosana (Hayata) Rehder is the dominant species in the temperate forest of Yuanyang Lake Nature Reserve (YYL), Taiwan. Although downed logs of C. obstusa var. formosana occupy only a small percentage of the forest floor area in YYL, they are important regeneration substrates. Seedlings of this species often grow without competition on the new downed logs, and a few broadleaf trees grow with them. We hypothesized that the bark of the newly fallen logs possesses allelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The observed regeneration of C. obtusa and coexisting Rhododendron spp. on deadwood supports the findings of previous studies (Yamamoto 1993;Liao et al 2003;Tseng et al 2007). Both C. obtusa and Rhododendron spp.…”
Section: Discussionsupporting
confidence: 92%
“…The observed regeneration of C. obtusa and coexisting Rhododendron spp. on deadwood supports the findings of previous studies (Yamamoto 1993;Liao et al 2003;Tseng et al 2007). Both C. obtusa and Rhododendron spp.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Duryea et al (1999) observed allelopathic effects of several fresh mulches in bioassays on germination of lettuce seeds. Salicylic acid from bark of Chamaecyparis obtusa induced allelopathic effects on seeds of plants native to the species' range in Taiwan as well as on seeds of exotic plants (Tseng et al, 2007). Allelopathic effects on newly planted or existing woody landscape plants, however, have not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…formosana (Hayata) Rehder (Cupressaceae) is a coniferous and native tree that grows at elevations of 1800–2600 m and is indigenous to Taiwan. It has been used as a medicinal plant in Taiwan and has various biological activities such as antitermitic activity, allopathic activity, cytotoxicity against carcinoma cell lines, antioxidant activity and delayed aging effects . Moreover, the hot water extract (HWE) from C. obtusa var.…”
Section: Introductionmentioning
confidence: 99%